Extracts of renealmia alpinia (Rottb.) MAAS protect against lethality and systemic hemorrhage induced by bothrops asper venom: insights from a model with extract administration before venom injection (2015)
Renealmia alpinia (Rottb.) MAAS, obtained by micropropagation (in vitro) and wild forms have previously been shown to inhibit some toxic activities of Bothrops asper snake venom if preincubated before injection. In this study, assays were performed in a murine model in which extracts were administered for three days before venom injection. R. alpinia extracts inhibited lethal activity of B. asper venom injected by intraperitoneal route. Median Effective Dose (ED50) values were 36.6 ± 3.2 mg/kg and 31.7 ± 5.4 mg/kg (p > 0.05) for R. alpinia wild and in vitro extracts, respectively. At a dose of 75 mg/kg, both extracts totally inhibited the lethal activity of the venom. Moreover, this dose prolonged survival time of mice receiving a lethal dose of venom by the intravenous route. At 75 mg/kg, both extracts of R. alpinia reduced the extent of venom-induced pulmonary hemorrhage by OPEN ACCESS Toxins 2015, 7 1533 48.0% (in vitro extract) and 34.7% (wild extract), in agreement with histological observations of lung tissue. R. alpinia extracts also inhibited hemorrhage in heart and kidneys, as evidenced by a decrease in mg of hemoglobin/g of organ. These results suggest the possibility of using R. alpinia as a prophylactic agent in snakebite, a hypothesis that needs to be further explored.